On the occurrence of amphibolite-facies sapphirine, spinel, phlogopite, anorthite, and corundum in the Wet Mountains, Colorado, USA - Palin, RM; Palmer, Z; Holm-Denoma, C; Hernández-Uribe, D; Hernández-Montenegro, JD (Elsevier, 2023)
The Wet Mountains, southern Colorado, expose Mesoproterozoic metamorphic and magmatic rocks that record the early deformational history of the west–central continental USA and growth of Laurentia. Of particular petrological interest are halogen-enriched metamorphic rocks adjacent to the San Isabel A-type granite, situated in the southern Wet Mountains, which contain sapphirine, spinel, phlogopite, anorthite, and corundum. Conventional thermobarometry and phase diagram-based thermodynamic modeling indicates peak pressure–temperature (P–T) conditions of metamorphism within the upper amphibolite facies (∼750–770 °C) at middle-crustal pressures (∼6–7 kbar), and in-situ U-Pb geochronology of monazite constrains peak metamorphism to c. 1340–1320 Ma. These sapphirine-hornfels units are younger than metamorphic lithologies elsewhere in the southern Wet Mountains (c. 1430 Ma), but only slightly post-date the timing of intrusion of the granite itself (1362 ± 7 Ma). These rocks are thus interpreted to be of contact metamorphic origin, with high F contents in mica and amphibole interpreted to record metasomatism in the middle crust by halogen-rich fluids expelled by the San Isabel granite. However, as the temperature of emplacement and crystallization of the granite likely did not greatly exceed 800–850 °C, these rocks document an unusual occurrence of normally granulite-facies and (ultra)high-temperature metamorphic minerals stabilizing at lower grade. Thus, caution must be used when using such parageneses as field indicators of geodynamic settings associated with extreme heat flow, such as continental rifting and/or voluminous emplacement of dry, mafic magma.